Mapping the Transformation of Political Participation through Digital Citizenship: Global Trends from a Bibliometric Analysis (2019–2024) - Atikah Fadilla; Dian Eka Rahmawati (INJECT (Interdisciplinary Journal of Communication), 2025)
This study investigates the transformation of political participation in the era of digital citizenship, where information and communication technologies have reshaped how citizens engage in democratic processes. Moving beyond traditional notions of rights and obligations, citizenship is increasingly characterized by the ability to participate actively in public affairs through digital platforms. Using a bibliometric analysis of 339 Scopus-indexed articles published between 2019 and 2024, this research maps publication trends, conceptual clusters, and thematic evolutions related to digital citizenship and political participation. The findings reveal four dominant clusters: digital citizenship, citizenship, political participation, and digital transformation that organize the field, with emerging themes such as COVID-19, gender, and digital education policies shaping more recent scholarship. Results highlight the strategic role of digital technologies in enabling political campaigns, online petitions, e-voting, and social media activism while exposing persistent challenges such as misinformation, privacy concerns, and digital divides. This study contributes to the literature by offering a comprehensive mapping of global scholarship, clarifying conceptual linkages, and identifying research gaps related to inclusivity and cross-regional comparisons. Strengthening digital and media literacy is crucial to ensure more inclusive, ethical, and meaningful forms of political participation in the digital age.